Correlates and Timing of Reproductive Aging Transitions in a Global Cohort of Midlife Women With Human Immunodeficiency Virus: Insights From the REPRIEVE Trial - Zanni, Markella V (J Infect Dis, 2020)
BACKGROUND: Reproductive aging may contribute to cardiometabolic comorbid conditions. We integrated data on gynecologic history with levels of an ovarian reserve marker (anti-müllerian hormone [AMH)] to interrogate reproductive aging patterns and associated factors among a subset of cisgender women with human immunodeficiency virus (WWH) enrolled in the REPRIEVE trial. METHODS: A total of 1449 WWH were classified as premenopausal (n = 482) (menses within 12 months; AMH level ≥20 pg/mL; group 1), premenopausal with reduced ovarian reserve (n = 224) (menses within 12 months; AMH <20 pg/mL; group 2), or postmenopausal (n = 743) (no menses within12 months; AMH <20 pg/mL; group 3). Proportional odds models, adjusted for chronologic age, were used to investigate associations of cardiometabolic and demographic parameters with reproductive aging milestones (AMH <20 pg/mL or >12 months of amenorrhea). Excluding WWH with surgical menopause, age at final menstrual period was summarized for postmenopausal WWH (group 3) and estimated among all WWH (groups 1–3) using an accelerated failure-time model. RESULTS: Cardiometabolic and demographic parameters associated with advanced reproductive age (controlling for chronologic age) included waist circumference (>88 vs ≤88 cm) (odds ratio [OR], 1.38; 95% confidence interval, 1.06–1.80; P = .02), hemoglobin (≥12 vs <12 g/dL) (2.32; 1.71–3.14; P < .01), and region of residence (sub-Saharan Africa [1.50; 1.07–2.11; P = .02] and Latin America and the Caribbean [1.59; 1.08–2.33; P = .02], as compared with World Health Organization Global Burden of Disease high-income regions). The median age (Q1, Q3) at the final menstrual period was 48 (45, 51) years when described among postmenopausal WWH, and either 49 (46, 52) or 50 (47, 53) years when estimated among all WWH, depending on censoring strategy. CONCLUSIONS: Among WWH in the REPRIEVE trial, more advanced reproductive age is associated with metabolic dysregulation and region of residence. Additional research on age at menopause among WWH is needed. CLINICAL TRIALS REGISTRATION: NCT0234429.